THE INFLUENCE OF THE ROLE OF POSYANDU CADRES ON THE OPTIMIZATION OF POSYANDU IN PREVENTING STUNTING IN THE MUARA SATU HEALTH CENTER IN LHOKSEUMAWE CITY - Frisca Fazira; Risna Fazlaini; Fitria Fitria; Fitri Hijri Khana; Nisrina Hanum (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Malnutrition conditions over a long period of time have an impact on reducing the quality of life of children in the future and have succeeded in attracting world attention, including Indonesia. In SDG's 2030 Indonesia targets to end hunger as the second goal by reducing the prevalence of stunting in toddlers by 2025. Effective implementation of posyandu in accordance with technical instructions will certainly reduce the incidence of stunting in toddlers, especially optimization in steps IV and V of posyandu, namely providing health education by cadres and health services by health workers. The aim of this research is to determine the influence of the role of posyandu cadres on the optimization of posyandu in preventing stunting in the working area of Muara Satu Health Center, Lhokseumawe City in 2024. This type of research is analytical observational research using a cross sectional approach. The population in this study were posyandu cadres in the working area of the Muara Satu Health Center, Muara Satu District, Lhokseumawe City in 2024. The sample for this study was purposive sampling, namely all posyandu cadres in the Muara Satu Community Health Center working area, Muara Satu District, Lhokseumawe City. The results of the study showed that the oral motor skills of babies aged 6-12 months before the role of active cadres in preventing stunting in the Muara Satu Community Health Center Working Area, Lhokseumawe City were in the active category, namely 71 people (94.7%) and 4 people (5,3%) who were inactive. Optimization of posyandu in preventing stunting in the Muara Satu Community Health Center Working Area, Lhokseumawe City in the Yes category, namely 67 people (89.4%) and 8 people (10.6%) who were inactive. The role of posyandu cadres influences the optimization of posyandu in prevention. stunting in the working area of Muara Satu Health Center, Lhokseumawe City in 2024 p=0.000 <0.05. It is hoped that posyandu cadres will have the motivation and awareness to carry out health efforts, especially regarding stunting prevention so that the incidence of stunting in toddlers can be prevented and the health status of babies and toddlers will improve.